A NEW METHOD FOR QUANTIFICATION OF REGENERATED BONE TISSUE ON X-RAY IMAGES OF ELONGATED BONES - Gądek, Aneta; Wojnar, Leszek; Tęsiorowski, Maciej; Jasiewicz, Barbara (Image Analysis and Stereology, 2011)
A new method for quantification of bone regenerate on the basis of computer-aided analysis of digitized Xray images is presented and its applicability in bone lengthening using Ilizarov method is demonstrated. In contrary to classical methods the internal part of the bone image is taken into consideration instead of the bone edges. Theoretical background of this concept is presented and experimentally verified. Experimental results show that the method proposed allows us for assessment of the bone regenerate, precise choice of the moment of external fixator removal as well as prediction of abnormalities in the osteogenesis process (excluding overall decalcification). However, the rules of interpretation of the results are not discussed in details.